2018
DOI: 10.3892/etm.2018.6203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin D deficiency on T cell subsets and related indices during spinal tuberculosis

Abstract: The present study investigated the effects of vitamin D deficiency on T cell subsets in patients with spinal tuberculosis. In addition, the influence of vitamin D deficiency was investigated on the expression of cytokines IL-1β, IL-6 and TNF-α in intervertebral disc lesions of patients. One hundred and seventeen patients with spinal tuberculosis who received operative treatment in the Department of Orthopedics in Wuhan City Third Hospital from March 2012 to March 2015 were collected. The patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(19 reference statements)
0
8
0
2
Order By: Relevance
“…In experimental models it down-regulates the immune responses mediated by T helper (Th) 1 cells, thus inhibiting the production of pro-inflammatory cytokines, such as Interferon-γ IFN-γ, IL-6, IL-2, and TNF-α [ 66 , 67 ]. Although experimental studies in vitro and in animals have yielded encouraging results on the immunomodulatory effect of 1,25(OH) 2 D 3 , the same cannot be said about human studies, and few studies have confirmed the suppressive effect of vitamin D on Th1 cells and inflammatory cytokine production in different diseases and spinal tuberculosis [ 68 ], uremia [ 69 ], and autoimmune thyroiditis [ 70 ]; whereas others in IBD [ 71 ], dialysis [ 72 ], and rheumatoid arthritis [ 73 ] do not confirm these results. These discrepancies may be due to the different diseases considered and also to the different type of treatment administered, mainly 1,25(OH) 2 D 3 in vitro and in animals and vitamin D 3 in vivo in humans.…”
Section: Vitamin D and The Adaptive Immune Systemmentioning
confidence: 99%
“…In experimental models it down-regulates the immune responses mediated by T helper (Th) 1 cells, thus inhibiting the production of pro-inflammatory cytokines, such as Interferon-γ IFN-γ, IL-6, IL-2, and TNF-α [ 66 , 67 ]. Although experimental studies in vitro and in animals have yielded encouraging results on the immunomodulatory effect of 1,25(OH) 2 D 3 , the same cannot be said about human studies, and few studies have confirmed the suppressive effect of vitamin D on Th1 cells and inflammatory cytokine production in different diseases and spinal tuberculosis [ 68 ], uremia [ 69 ], and autoimmune thyroiditis [ 70 ]; whereas others in IBD [ 71 ], dialysis [ 72 ], and rheumatoid arthritis [ 73 ] do not confirm these results. These discrepancies may be due to the different diseases considered and also to the different type of treatment administered, mainly 1,25(OH) 2 D 3 in vitro and in animals and vitamin D 3 in vivo in humans.…”
Section: Vitamin D and The Adaptive Immune Systemmentioning
confidence: 99%
“…Other studies in Malaysia and northern Iran reported higher levels of vitamin D in rural residents than in urban residents, as their exposure to the sun was greater [ 14 15 ]. In contrast, others reported lower levels of serum vitamin D in rural residents than in urban dwellers [ 16 17 ]. In our study, we were interested in women working in greenhouses as well as those who live in rural areas because greenhouses in Korea, which are covered with vinyl, not glass, restrict the exposure of these women to UV light, which is essential for vitamin D synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite strong experimental evidence, human studies are less convincing to prove a role for VD in the modulation of adaptive immune system of individuals affected by autoimmune diseases. In this respect, some trials have confirmed beneficial effect of VD on different inflammatory disease progression, inflammatory markers, and T cell subsets, whereas others have not shown any promising result [10,11].…”
Section: Role Of Vitamin D In Immune Regulation and Inflammatory Respmentioning
confidence: 99%